(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the difficulties which hinder the Muslim patients with urinary catheters in offering regular prayers and help them solve those difficulties. Design: A descriptive study. Place and Duration of Study: The study was conducted in the department of Urology Foundation University Medical College and Fauji Foundation Hospital Rawalpindi from July 2008 to December 2009. Inclusion Criterion: Muslim ambulant and mentally alert patients between the age 20 to 70 having a urinary catheter (urethral or suprapubic) were included in the study. Patients and Methods: 500 volunteer patients from both genders fulfilling the inclusion criterion were included in the study. Patients were given a questionnaire and asked about their regularity regarding offering of prayers before the insertion of urinary catheter and any change in that aspect after the catheter was placed. They were asked to mention the hindrance faced by them in offering their regular prayers after they got the urinary catheter. Results: Before insertion of the urinary catheter 39.2% patients were offering their prayers regularly, while after having been catheterized only 0.4% patients remained regular in their prayers. 30% mentioned about the urinary leakage alongside the catheter as a hindrance to prayers. 28% said they did not know how to perform Wudhu (washing of arms up to elbows, face and feet, and touching the hair on the front of the head with water) while they had a catheter inserted. 12% described urethral pain as a hindrance to offer prayers. Remaining 29.6% gave no reason for abandoning regular prayers. However, all the patients wished they could pray. Those patients complaining about urine leakage were managed. Those who did not know how to perform Wudhu in this situation were guided. Patients complaining of pain due to catheter were treated. Those who could give no reason were counseled. A positive approach on the part of the patients was observed after these measures. Conclusion: Muslim patients having a urinary catheter can offer regular prayers. Urinary catheter is not a hindrance to prayers. Patients need to be counseled accordingly.